Spite vs. risk: explaining overbidding - Oliver Kirchkamp; Wladislaw Mill (Center for Economic Studies and ifo Institute (CESifo), 2019)
In this paper we use an experiment to compare a theory of risk aversion and a theory of spite as an explanation for overbidding in auctions. As a workhorse we use the second-price all-pay and the first-price winner-pay auction. Both risk and spite can be used to rationalize deviations from risk neutral equilibrium bids in auctions. We exploit that equilibrium predictions in the second-price all-pay auctions for spiteful preferences are different than those for risk averse preferences. Indeed, we find that spite is a more convincing explanation for bidding behavior for the second-price all-pay auction. Not only can spite rationalize observed bids, also our measure for spite is consistent with observed bids.
Keywords: C91; C72; D44; D91; 330; auction; overbidding; spite; risk; experiment